PEMBERDAYAAN EKONOMI BERLANDASKAN MASLAHAH DALAM HUKUM ISLAM - Muhibban; Munir , Muhammad Misbakul (Institut Agama Islam Sahid (INAIS) Bogor, 2023)
This study aims to explore economic empowerment within the framework of Islamic teachings, emphasizing the principle of maslahah as its primary foundation. Through descriptive analysis and library research, the study highlights the central role of the maslahah principle in regulating Islamic economics, ensuring collective welfare, justice, and balance within economic dynamics. Findings reveal that this principle forms the basis of Islamic economic law, encompassing financial transaction regulations, resource distribution, corporate social roles, and financial institution structures, with a focus on ethical values and social responsibilities. Maslahah based economic empowerment not only pursues material growth but also contributes to social welfare, justice, and environmental sustainability, reinforcing the significance of implementing these values within Islamic economic practices.